Molecular survey on Merkel cell polyomavirus in patients with colorectal cancer (Medical Journal of Indonesia, 2018)
Background: Merkel cell polyomavirus (MCV) has been associated with Merkel cell carcinoma (MCC) in humans, and its role in other human cancers is under investigation. The aim of this study was to investigate MCV genome infection in patients with colorectal cancer (CRC).Methods: This retrospective, case-control study used archived formalin-fixed, paraffin-embedded (FFPE) tissue samples from colorectal cancer patients (cases) and matched healthy subjects (controls) diagnosed by an expert pathologist from hospitals affiliated with Iran University of Medical Sciences, Tehran, Iran from 2011 to 2016. After DNA extraction with a QIAamp® DNA FFPE Tissue Kit, real-time polymerase chain reaction (PCR) was used for diagnosis. A positive control was produced by cloning with the Generay Biotechnology system. SPSS v.22 was used for analysis of demographic variables.Results: There were 157 participants included in the study: 66 were cases and 91 were controls. Their mean ages (±SD) were 59.35±14.48 and 57.21±14.66, respectively. The proportion of males was 57.6% in the case group and 57.1% in the control group. None of the samples were positive for MCV expression by real-time PCR assay. Association was detected between males with CRC and tumor location in the rectum and between males with CRC and the mucinous tumor type.Conclusion: None of the tissues from the CRC or non-cancerous control groups were positive for MCV genome infection, although a low viral load, the sample type, or the method of use should not be neglected. Further studies are recommended to obtain more comprehensive results.